Organisational Culture as The Primary Barrier to Public Sector Performance Reform Presented (African Journal of Public Administration & Management, 2026)
Reforms globally fail when culture remains unchanged (Grindle, 2017). AU Agenda 2063: mindset change foundation for institutional transformation (AU,2015).
Keywords: Public Sector Performance Reform; Organisational Culture